Marketing to Moviegoers : A Handbook of Strategies and Tactics, Third Edition - Marich, Robert (Book collections on Project MUSE., 2013)
While Hollywood executives spend millions of dollars making movies, even more money is poured into selling those films to the public. In the third edition of this guidebook, a veteran film and TV journalist plumbs the depths of the methods used by studios to market their films to consumers. Updates to the third edition include a chapter on marketing movies using digital media; an insightful discussion of the use of music in film trailers; expanded materials on marketing targeted toward affinity groups and awards; fresh analysis of booking contracts between theaters and distributors; a brief history of indie film marketing; and explorations of the overlooked potential of the drive-in theater and the revival of third-party-financed movie campaigns.